Explicitation Translation Strategy Regarding Indonesian Political Situation in the Novel ‘Home’ Pulang - Taufik Ampera,; Mahmud, Erlina Zulkifli; Sidiq, Inu isnaeni (International Journal of Psychosocial Rehabilitation, 2020)
This research discusses how Indonesian political situation expressed in an Indonesian novel entitled Pulang and how the expressions are translated into English language in ‘Home’. By applying explicitation translation strategy, this research aims to reveal what specific information are explicitated and what form of explicitation is used. Using descriptive-comparative method the analysis is performed. The explicitation translation strategy used is of Vinay and Darbelnet which has been elaborated by Klaudy and Karoly (2005). To find out the form of explicitation occurred in the target language text, the categorization of explicitation by Seguinot (1988) is applied. The result shows that the specific information which is explicitated deals with identity; actors in pronouns, names of organization or institution, names of people; and locations; also it deals with activity; from passive to active and vice versa; and the forms of explicitation involved are all the three of them. This research does not use any other Studies except Translation Studies. By this research, the efforts of the translator to provide the equivalents of expressions regarding Indonesian political situation as equal as possible can be observed. This article is originally made and has never been published before and is not being reviewed for any other publication.